CHARACTERISTICS OF GLASS SOAP BASED ON VIRGIN COCONUT OIL (VCO) WITH THE ADDITION OF BASIL LEAF EXTRACT (OCIMUM BASILICUM L.) AS ANTISEPTICS - Meilianti; Idha Silviyati; Adi Syakdani (Politeknik Negeri Sriwijaya, 2022)
Soap is formed from a mixture of fat or oil with sodium or potassium salts made through the saponification process ofthe reaction between triglycerides and alkali. Glass soap is a innovation in the form of solid soap which has a smallsize in the form of a thin sheet that is easier to carry when active outside the home. Basil leaves contain flavonoid,tannins, saponins and other active ingredients that can be used as antibacterial. Glycerin can be used as a mixture insoap making as a plasticizer because it can make the texture of the soap elastic. The process of making glass soapuses a saponification process with variations in the addition of glycerin concentrations (w/w) of 5.5%, 10.5%, 15.5%,20.5%, 25.5% in curing time for 15 days. The results of the analysis showed that glass soap with the addition of 10%glycerin concentration with a curing time of 15 days was the best formulation and met the characteristics of SNI. Theresults of the analysis showed that the water content was 0.45%, the material was insoluble in ethanol 1.20%, ALB1.5%, free alkali 0.05%, and pH 10.